Protective Effects of Sesamin on Cytoxan-Induced Spermatogenesis Dysfunction by Regulating RNF8-ubH2A/ubH2B Pathways in Male Mice - Hai, Dong-Mei; Ren, Jia-Wei; Chi, Yan-Nan; Ye, Rui-Juan; Liu, Ning; Ma, Lin; Lan, Xiao-Bing; Wu, Jing; Yu, Jian-Qiang; Yang, Jia-Mei (Frontiers in Pharmacology, 2021)
In clinical infertile patients, most of them show spermatogenesis dysfunction. Cyclophosphamide, as an anticancer drug, can cause spermatogenesis dysfunction model. Sesamin is the main bioactive component of natural lignans in sesame. It is abundant in sesame oil and has strong biological activities such as antioxidant, antibacterial and hypoglycemic. By establishing the model of spermatogenic dysfunction induced by cyclophosphamide in male mice and feeding sesamin (50, 100, 200 mg/kg) for 2 weeks, we proved that sesamin can improve the reproductive organ damage induced by cyclophosphamide, and increase the number and activity of sperm. Sesamin can resist cyclophosphamide induced Sperm nuclear maturity and DNA damage by increasing the expression levels of histone H2A and H2B in testis. In addition, sesamin can improve the ubiquitination of histone regulated by RNF8 to protect testis. In conclusion, these results suggest that sesamin can improve spermatogenic dysfunction induced by cyclophosphamide, which may be mediated by ubiquitination of histone.